JATROPHA CURCAS REPAIRING EFFECT ON ADHESION MOLECULES, DNA DAMAGE AND GENE EXPRESSION ALTERATION IN STZ-INDUCED DIABETIC RATS - FAROUK K. EL-BAZ; HANAN F. ALY; WAGDY K. B. KHALIL; HODA F. BOOLES; SAFAA A. SAAD (International Journal of Pharma and Bio Sciences, 2015)
The recent research converges on the evaluation of Jatropha curcas different extracts on some biochemical parameters in streptozotocin (STZ)-induced diabetic rats. Diabetes mellitus (DM) was induced using STZ (45 mg/kg b.w) while, J. curcas extracts were orally administered at a dose of 250mg/kg/day and glibenclamide (antidiabetic drug) at a dose of 10mg/kg/day for 30 days. Adhesion molecules; VCAM-1 and ICAM-1 were measured in blood serum of rats and the results showed that VCAM-1 and ICAM-1 levels were significantly increased in diabetic rats as compared to controls. The results showed that J. curcas extracts have reduced VCAM-1 and ICAM-1 high levels in diabetic rats. DNA fragmentation was determined using diphenylamine reaction as well as DNA gel electrophoresis laddering assays and the expression of diabetes related genes was determined by qRT-PCR. The results revealed that the administration of J. curcas extracts exhibited relatively the rates of DNA damage similar to those in the control group. Moreover, J. curcas extracts altered the expression of diabetes related genes and appeared similar to those in control group. Thus, J. curcas extracts might be a promising regulator supplement for hyperglycemia and the expression of genes related DM.